2003
DOI: 10.4102/jsava.v74i1.488
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of cotyledoside following intravenous administration to sheep

Abstract: INTRODUCTIONKrimpsiekte, a chronic form of cardiac glycoside poisoning, manifests as a paretic syndrome and occurs predominantly in small stock 5,6 . The disease develops following ingestion of certain members of the Crassulaceae (Cotyledon, Tylecodon and Kalanchoe species). Krimpsiekte is generally believed to be caused by cumulative bufadienolides, with unique neurotoxic properties, encountered in these genera 5,7 . Naudé and Schultz 8 coined the term 'cumulative bufadienolides' following the successful demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
1
7
1
1
Order By: Relevance
“…There are conflicting reports in the literature regarding the ability of tetrathiomolybdate to increase copper excretion in the urine 3,9,14 , but in this experiment the molybdate therapy did not significantly increase cupruresis in relation to the other groups (Fig. 4).…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…There are conflicting reports in the literature regarding the ability of tetrathiomolybdate to increase copper excretion in the urine 3,9,14 , but in this experiment the molybdate therapy did not significantly increase cupruresis in relation to the other groups (Fig. 4).…”
Section: Discussioncontrasting
confidence: 39%
“…It is surmised that the TCA-insoluble copper is not taken up by red blood cells and this inability to penetrate erythrocytes is the reason why haemolysis is not precipitated and increased urinary copper excretion occurs 9 . Other researchers reported that tetrathiomolybdate treatment had no effect on the rate and amount of copper excreted in the urine 3,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Quanto aos valores séricos, estes são inferiores aos encontrados por diferentes autores. Van Ryssen & Stielau (1981) encontraram valores de 0,63 ±0,21μmol/L, quando avaliaram o efeito de diferentes ní-veis de Mo dietético no metabolismo do Cu e Mo em ovinos alimentados com elevados teores de Cu e S. Botha et al (1995), encontraram 0,52 ±0,42μmol/L, estudando a farmacocinética do tetratiomolibdato em ovinos e Antonelli (2007), encontrou teores séricos de 0,8±0,19μmol/L, quando estudou o efeito do uso de sal mineral rico em Mo na intoxicação cúprica cumulativa. Apenas Pott et al (1999), avaliando o efeito de dietas com elevado teor de Mo no metabolismo do Mo e Cu em ovinos, encontraram valor médio de Mo hepático (0,10μmol/L) inferior aos encontrados neste estudo.…”
Section: Discussionunclassified
“…An elimination half-life (T1/2 beta) of 396.8 min, steady state volume of distribution (Vdss) of 0.8 e kg-1 and total body clearance (C1B) of 1.53 ml kg-1 min-1 were observed using non-linear compartmental analysis. A significant (p < or = 0.05) increase in molybdenum excretion in the faeces occurred at 24 and 48 h following TM administration [61]. …”
Section: Copper Reduction As An Anti-cancer Strategymentioning
confidence: 99%